2010
DOI: 10.1128/jvi.01087-10
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function Analysis of Therapeutic Monoclonal Antibodies against Dengue Virus Type 2

Abstract: Dengue virus (DENV) is the most prevalent insect-transmitted viral disease in humans globally, and currently no specific therapy or vaccine is available. Protection against DENV and other related flaviviruses is associated with the development of antibodies against the viral envelope (E) protein. Although prior studies have characterized the neutralizing activity of monoclonal antibodies (MAbs) against DENV type 2 (DENV-2), none have compared simultaneously the inhibitory activity against a genetically diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
199
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(207 citation statements)
references
References 72 publications
7
199
0
1
Order By: Relevance
“…Although the use of DIII alone as an antigen for DENV vaccine development has been proved to induce antibodies against neutralizing E epitopes (Pierson et al, 2008;Poggianella et al, 2015), recent data have demonstrated the presence of broadly neutralizing antibodies directed against epitopes on DI and DII (Sukupolvi-Petty et al, 2010;Wahala et al, 2009;Williams et al, 2012), and on E dimers (envelope dimer epitopes) that are reactive with all four serotypes Rouvinski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the use of DIII alone as an antigen for DENV vaccine development has been proved to induce antibodies against neutralizing E epitopes (Pierson et al, 2008;Poggianella et al, 2015), recent data have demonstrated the presence of broadly neutralizing antibodies directed against epitopes on DI and DII (Sukupolvi-Petty et al, 2010;Wahala et al, 2009;Williams et al, 2012), and on E dimers (envelope dimer epitopes) that are reactive with all four serotypes Rouvinski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since most of neutralizing epitopes on E appear to be conformational in nature (Sukupolvi-Petty et al, 2010), obtaining the E protein in its native conformation is critical for the development of an efficient vaccine against DENV . Several C-terminal truncated versions of E, in which the stem and the transmembrane anchor of the protein have been removed, have been developed for DNA and protein subunit immunizations (Coller et al, 2011;Guzmán et al, 2003;Mani et al, 2013;Ocazionez Jimenez & Lopes da Fonseca, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). The G330D substitution occurs naturally and is characteristic of the DENV-2 sylvatic genotype (Chambers et al, 1990;Pitcher et al, 2012;Sukupolvi-Petty et al, 2010).…”
mentioning
confidence: 99%
“…Therefore, we screened by ELISA a panel of mAbs to identify those with serotype-specific reactivity. Three murine mAbs, all binding E domain III (anti-DENV1 E95, anti-DENV2 E96, and anti-DENV4 E88) (17)(18)(19) and one human E domain I/II-directed mAb (anti-DENV3 5J7) (14,20), were selected. The epitopes targeted are maturation insensitive; thus, the maturation state of the virion should not affect binding of the detection mAbs (20,21).…”
Section: Optimization Of the Denv Qcfmentioning
confidence: 99%